First report of the association of Genus Chaetomium with roots of Cucurbita maxima - Jonathan D. Hulse (Novel Research in Microbiology Journal)
Chaetomium sp. is a fungal genus in the Ascomycota that has a world-wide distribution throughout tropic and temperate regions. Species of Chaetomium are often associated with and classified as both seed-borne and soilborne fungi, which inhabit a variety of terrestrial ecosystems including; agricultural, forests, grasslands, wetlands, and coastal zones. Chaetomium sp. plays an important ecological role as a saprophyte, but also shows strong antimicrobial activities which allow its use as a biological control agent (BCA). Chaetomium sp. has been recorded on the seeds and within the rhizosphere of a variety of genera of the family Cucurbitaceae including; Citrullus, Cucumis, Cucurbita, Lagenaria, and Luffa. Within the genus Cucurbita, Chaetomium sp. has been documented in association with Cucurbita pepo and Cucurbita moschata, however up till now there is no record of association of Chaetomium sp. with Cucurbita maxima. Sampling of Cucurbita maxima roots in the eastern United States resulted in the discovery of a novel relationship between Cucurbita maxima and Chaetomium sp. This manuscript presents the first report of existence of a relationship between Chaetomium sp. and Cucurbita maxima, with the aid of light microscope to image the perithecia and spores produced by this fungus.